ADAPTATION OF INDEPENDENT LEARNING CURRICULUM IN THE IMPLEMENTATION OF LEARNING IN CLASS IVA AL FALAH ASSALAM ELEMENTARY SCHOOL - Muti Syarofani; Muhammad Dwi Santoso; Mutiarizki Hapsari; Refi Mariska Anggraini; Maadhin Fiyya Huk Muka; Alissa Putri Maharani (El Midad, 2023)
This study aims to determine the process of implementing the independent learning curriculum in class IV of Al Falah Assalam Elementary School after the use of the 2013 curriculum. This study used a qualitative approach. Data collection procedures are through observation, interviews, and documentary evidence. While the analysis of the data used is in the form of data collection, selecting data according to the problem, displaying data, and making conclusions. The results of this study indicate that (1) Al Falah Assalam Elementary School has used teaching modules as a reference in the Merdeka Learning curriculum replacing the lesson plans in the revised 2013 curriculum. (2) The learning process in the class uses differentiation learning based on learning styles and types of abilities, diagnostic results, and student personalities, (3) There are no significant obstacles for Al Falah Assalam school in the trial transition from the revised 2013 curriculum to the independent learning curriculum